The deeds of Pope Innocent III - Powell, James M. (Washington, DC. : Catholic University of America Press, 2004)
"The Deeds of Pope Innocent III, composed before 1210 by an anonymous member of the papal curia, provides a unique window into the activities, policies, and strategies of the papacy and the curia during one of the most important periods in the history of the medieval church. Innocent III, who became pope in 1198 and reigned until 1216, has long been regarded as one of the most important popes in history." "This partial biography covering the first ten years of Innocent's pontificate was written by a cleric close to the pope and familiar with the curia. The translator, James M. Powell, suggests that it was written by the canonist and later cardinal Peter of Benevento. Peter had a profound knowledge of southern Italy and closely followed Innocent's efforts to unify the churches of the East and West and to promote the crusade." "The translator provides an engaging introduction and adds numerous explantory notes throughout the book. Those who seek a fuller understanding of the development of the papacy during a period of great change in medieval religious history will find this work essential"--BOOK JACKET.
Family, education, election -- Rome and the Papal states -- The kingdom of Sicily -- Spiritual concerns -- The crusade and church unity -- Peter of Aragon in Rome -- The Papal states -- Papal concerns with the churches -- Rome, again! -- Works of piety: the gift list.
Translated into English from the Latin.
Includes bibliographical references (pages 275-279) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Innocent -- III, -- Pope, -- 1160 or 1161-1216.; Innocent -- III, -- pape, -- 1160 ou 61-1216.; Innocent -- III, -- Pope, -- 1160 or 1161-1216; Gesta Innocentii III; Innocent -- Iii -- Papa, -- 1160 Or 61-1216.; Innocent -- III -- (pape ; -- 1160-1216); Innozenz -- Papst, III; Papacy -- History; Papauté -- Histoire; RELIGION -- Christianity -- Catholic; HISTORY -- Medieval; Papacy; Papst; História eclesiástica.; Igreja católica (história); Biografias; Papauté -- Histoire; History